2019
DOI: 10.1002/tee.22961
|View full text |Cite
|
Sign up to set email alerts
|

Study on sensitivity characteristic of capacitive coupler for PD detection in HV cable joint

Abstract: The capacitive coupler is an attractive tool for on-site partial discharge (PD) detection in a cable joint. To study its sensitivity characteristic, PDs in a 110-kV prefabricated joint containing two artificial defects were detected successively using capacitive couplers with six different electrode widths installed at the same position of the cable. For the quantification of sensor sensitivity, the sensitivity factor is defined as the ratio of capacitive coupler output voltage amplitude to apparent charge tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…That paper commented that methods were inappropriate for on-line quantification of calibration of cable joints due to attenuation of the pulses within the cable and reflection at the cable terminations which introduced significant errors. On the other hand, this study (Ruan et al, 2019) reported sensitivity of the couplers ranging from 0.04 to 1.2 mV per pC. That study revealed the couplers were insensitive to some defects which could results into dead zones during PD detection.…”
Section: Capacitive Coupler Quantificationmentioning
confidence: 61%
See 1 more Smart Citation
“…That paper commented that methods were inappropriate for on-line quantification of calibration of cable joints due to attenuation of the pulses within the cable and reflection at the cable terminations which introduced significant errors. On the other hand, this study (Ruan et al, 2019) reported sensitivity of the couplers ranging from 0.04 to 1.2 mV per pC. That study revealed the couplers were insensitive to some defects which could results into dead zones during PD detection.…”
Section: Capacitive Coupler Quantificationmentioning
confidence: 61%
“…The quantification results obtained may not only depend on magnitude of the injected pulse, but also its wave form and its frequency spectrum that reaches the detector (Halim et al, 2021;Kirkcaldy et al, 2019;Ruan et al, 2019). The experiments done by Tian et al, (2002) indicated a nearly relationship between A and q which gives the quantification results of approximately 0.7 mV per pC when the pulse was injected at the cable termination.…”
Section: Capacitive Coupler Quantificationmentioning
confidence: 99%